The invasive parasitic fly Philornis downsi is threatening Little Vermilion Flycatchers on the Galápagos Islands - Denis Mosquera; Birgit Fessl; David Anchundia; Eileen Heyer; Celina Leuba; Erwin Nemeth; Maria Lorena. Rojas; Christian Sevilla; Sabine Tebbich (Avian Conservation and Ecology, 2022)
Populations of several species of birds endemic to the Galápagos Islands have declined during recent decades, including endemic Little Vermilion Flycatchers (Pyrocephalus nanus). Understanding the reasons for the low breeding success of this species is a prerequisite for developing efficient conservation strategies. Studies of sympatric Darwin’s finches suggest two potential reasons: parasitism by the invasive parasitic fly Philornis downsi and extreme climatic events. We investigated the role of each in the breeding success of Little Vermilion Flycatchers during three breeding seasons in the agricultural zone of Isabela Island. We found that Little Vermilion Flycatchers were severely affected by P. downsi, depending on the time of breeding. Nest success was high early in the breeding season (60% were successful) when rates of P. downsi prevalence and intensity were low, but nest success was zero and all nests were infested later in the breeding season. Philornis downsi prevalence and intensity increased with increasing temperature. Both low and high levels of rainfall had a negative effect on nest survival. A parasite removal experiment using insecticide confirmed the detrimental effect of the invasive parasite; nests infested with P. downsi had significantly lower nest success than treated nests. Injection of insecticide into nest bases can be an efficient short-term way to increase the nesting success of Little Vermilion Flycatchers, but finding long-term measures to control the P. downsi population is of utmost importance.